2014
DOI: 10.1093/nar/gku559
|View full text |Cite
|
Sign up to set email alerts
|

G-quadruplexes within prion mRNA: the missing link in prion disease?

Abstract: Cellular ribonucleic acid (RNA) plays a crucial role in the initial conversion of cellular prion protein PrPC to infectious PrPSc or scrapie. The nature of this RNA remains elusive. Previously, RNA aptamers against PrPC have been isolated and found to form G-quadruplexes (G4s). PrPC binding to G4 RNAs destabilizes its structure and is thought to trigger its conversion to PrPSc. Here it is shown that PrP messenger RNA (mRNA) itself contains several G4 motifs, located in the octarepeat region. Investigation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…Recent studies have shown that both DNA and RNA quadruplex structures bind PrP with a high affinity (44,46) and can modify the PrP conformation. It was shown that PrP can bind its own mRNA, which contains G4 motifs, causing it to form a quadruplex structure under particular conditions (47). It is becoming more and more obvious that PrP binds to structured nucleic acids, and both the nucleic acid and the protein undergo structural changes when this interaction occurs (29,43,44,48,49).…”
Section: Prp Requires Polyanions Such As Rna or Dna As Partners Durmentioning
confidence: 99%
“…Recent studies have shown that both DNA and RNA quadruplex structures bind PrP with a high affinity (44,46) and can modify the PrP conformation. It was shown that PrP can bind its own mRNA, which contains G4 motifs, causing it to form a quadruplex structure under particular conditions (47). It is becoming more and more obvious that PrP binds to structured nucleic acids, and both the nucleic acid and the protein undergo structural changes when this interaction occurs (29,43,44,48,49).…”
Section: Prp Requires Polyanions Such As Rna or Dna As Partners Durmentioning
confidence: 99%
“…One important example of such bistable stretches may be found in the mRNA of human cellular prion protein (PrP). Recent studies suggest that prion diseases (e.g., Creutzfeldt–Jakob disease) may, in fact, originate from the partial Qd conformers within PrP mRNA, which, under certain circumstances, may induce the formation of misfolded PrP . Due to the dynamic equilibrium and aggregation, characterization of the secondary structural species (G‐quadruplex/hairpin/single‐strand, Qd/Hp/Ss) and the determination of their molar fractions upon conformational transitions is complex.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the dynamic equilibrium and aggregation, characterization of the secondary structural species (G‐quadruplex/hairpin/single‐strand, Qd/Hp/Ss) and the determination of their molar fractions upon conformational transitions is complex. 1 H NMR, UV, and CD spectroscopic analyses of a bistable Qd/Hp RNA model (exhibiting an artificial fusion of Qd‐ and Hp‐forming sequences) and of Qd/Hp transitions within PrP mRNA have recently been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 One such characteristic connected with GQ affinity in some proteins is the presence of the stabilizing Arg-Gly-Gly (RGG) repeats as found for example in fragile X mental retardation protein, 18 nucleolin (a multifunctional heterogeneous nuclear ribonucleoprotein (hnRNP) belonging to the family of RNA binding proteins) 19 or engineered proteins. 20 GQ forming aptamers include for example nucleolinspecific DNA aptamer AS1411, 21 thrombin binding aptamer, 22 HIV1 aptamer T30177, 23 aptamers for prion proteins [24][25][26] or fluorophore binding aptamer spinach. 27 Another example is given by aptamer AIR-3 which has specificity for human interleukin-6 receptor (hIL-6R).…”
Section: Introductionmentioning
confidence: 99%